Peri-implant disease part 2: management of peri-implant disease. (2nd November 2019) - Daly, Alex; McCracken, Giles
Abstract : Unfortunately, peri-implant disease is a common clinical finding in patients with dental implants. Whilst preventive and supportive regimens are best practice, many patients still present with signs of peri-implant disease. Treatment options include non-surgical or surgical approaches but there does not appear to be a consensus for management of these challenging conditions. This paper discusses the current management options of peri-implant mucositis and peri-implantitis. CPD/Clinical Relevance: This paper discusses the management of peri-implant diseases placing emphasis on regular supportive care and follow up.